MECHANISM OF FORMING THE COMPETITIVENESS OF ENTERPRISES OF THE AIC IN THE CONDITIONS OF EXPORT-ORIENTED DEVELOPMENT (Development Service Industry Management, 2025)
The article explores the theoretical and methodological principles of the formation of the competitiveness of enterprises of the agro-industrial complex (hereinafter – AIC) in the context of increased export activity. The evolution of scientific approaches to the interpretation of the competitiveness category is summarized and the views of leading scientific schools on the role of innovations, resource potential, institutional changes and the ability of economic systems to adapt are systematized. The author's definition of the competitiveness of an enterprise as an integral characteristic of its ability to provide sustainable market advantages based on the effective use of resources, flexible response to changes in the external environment and the implementation of strategic management decisions is substantiated.Particular attention is paid to the analysis of the role of exports as a key factor in strengthening the competitive positions of enterprises of the AIC. The mechanism of interaction between enterprises of the AIC and exports is revealed, its structural components, functional purpose and critical success factors are determined. The coefficient of interaction of the export chain is proposed, which allows assessing the level of balance and efficiency of the export mechanism.The work developed a system of quantitative indicators to assess the impact of export activity on the competitiveness of enterprises of the AIC, in particular the export orientation index, price competitiveness coefficients, export efficiency and diversification of sales markets. The commodity and geographical structure of Ukraine's foreign trade, the dynamics of export prices and a SWOT-analysis of the export activity of enterprises of the AIC were analyzed.The practical value of the study lies in the possibility of using the proposed indicators and integral indicators to form and adjust export strategies of agribusiness enterprises in order to increase their long-term competitiveness in world markets.
Keywords: competitiveness; enterprises of the AIC; export activity; export potential; foreign trade; international markets